Phenomenal Woman: A Catalyst for Dismantling Patriarchal Norms - Shrestha, Surachhya (Journal of Balkumari College, 2024)
This paper aims to analyze Maya Angelou’s poem “Phenomenal Woman” as a catalyst for challenging conventional beauty norms and empowering women within the context of patriarchal structures. The main objective of this paper is to examine how the poem disrupts traditional perceptions of beauty and cultivates empowerment among women. This is a qualitative research; descriptive and analytical research design has been followed. The required information for the study has been gathered both from primary and secondary sources. The primary source of data is Maya Angelou’s poem “Phenomenal Woman”. Likewise, secondary data sources consist of books, journal articles, dictionary, encyclopedias, videos, and web browsers related to the works of Maya Angelou. Through a feminist lens, the paper analyzes the poem’s themes, language, and narrative to unveil the ways in which it challenges and defies traditional gender roles, promoting female empowerment and autonomy. The researcher also employs a close reading approach, which involves a detailed and in-depth examination of a particular text. This method focuses on understanding the language, structure, tone, style and figurative expressions of the poem. Lastly, the research questions have been answered. The key finding in the poem is celebration of womanhood, emphasis on inner strength, self-acceptance, confidence, women empowerment, and the beauty that goes beyond societal expectations.